Potency of Honje Hutan Flowers (Etlingera Hemisphaerica (Blume) R.M.Sm.) as Alpha-Glucosidase Inhibitor - Soraya Riyanti; Nandi Agustian; Akhirul Kahfi Syam (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
The Pangandaran people process honje flowers into fresh drinks that are consumed for health. Theforest honje leaf extract provides antidiabetic activity at a dose of 0.39 mg/g BW can reduce bloodglucose levels by 36.16% has been reported. Limited scientific information from honje hutan flowers,it is necessary on its activity as an alpha-glucosidase inhibitor and study its chemical content. Theextraction process was macerated in 70% ethanol for 24 hours and the fractionation process wascarried out by liquid-liquid extraction method with n-hexane, ethyl acetate and water as solvents.Testing the activity of alpha-glucosidase inhibitors colorimetrically using the chromogenic substratep-nitrophenyl α-D-glucopyranoside, alpha-glucosidase enzymes derived from Saccharomycescerevisiae, measurement of absorption at a maximum wavelength of 401.3 nm and acarbose usedas a comparison drug alpha-glucosidase inhibitors. The results showed that the forest honje flowerscontain flavonoids, polyphenols, tannins, quinones, monoterpenoids, and sesquiterpenoids. IC50 valuesfor 70% ethanol extract, n-hexane, ethyl acetate, water and acarbose fractions were 136.79, 307.18,277.12, 66.18, and 14.63 g/mL respectively. The water fraction gave the best inhibitory activity againstalpha-glucosidase with an IC50 value of 66.18 g/mL.Keywords: Etlingera hemisphaerica (Blume) R.M.Sm, honje hutan flowers, alpha-glucosidaseinhibitor.